2022
DOI: 10.3389/fcvm.2022.918033
|View full text |Cite
|
Sign up to set email alerts
|

Association between baseline smoking status and clinical outcomes following myocardial infarction

Abstract: BackgroundWhether the effect of smoking on clinical outcomes following an acute myocardial infarction (AMI) is beneficial or detrimental remains inconclusive. We invesetigated the effect of smoking on the clinical outcomes in patients following an AMI.MethodsAmong 13,104 patients between November 2011 and June 2015 from a nationwide Korean AMI registry, a total of 10,193 participants were extracted then classified into two groups according to their smoking habit: (1) smoking group (n = 6,261) and (2) non-smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Haig et al 18 established that smoking is strongly associated with inflammation and can be considered an independent causative factor of mortality or heart failure event. Similarly, smokers had a higher all-cause mortality and risk of re-hospitalization once the covariates were adjusted in a study conducted by Oh et al 29 Smoking was to be associated with higher mortality and risk of re-infarction. 16 Similarly, our study, on the other hand, prospectively enrolled STEMI patients, especially aiming at including all the covariates to control for that results in this paradoxical effect.…”
Section: Discussionmentioning
confidence: 90%
“…Haig et al 18 established that smoking is strongly associated with inflammation and can be considered an independent causative factor of mortality or heart failure event. Similarly, smokers had a higher all-cause mortality and risk of re-hospitalization once the covariates were adjusted in a study conducted by Oh et al 29 Smoking was to be associated with higher mortality and risk of re-infarction. 16 Similarly, our study, on the other hand, prospectively enrolled STEMI patients, especially aiming at including all the covariates to control for that results in this paradoxical effect.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, they had more STEMI and better LVEF than did the late presenters. These findings are sufficiently predictable, given that one clinical study revealed that smokers tend to have more STEMI and better LVEF than non-smokers [ 21 ]. Patients with STEMI tend to present complete occlusion of the infarct-related artery than those with NSTEMI [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 96%
“…The term “smoker's paradox” has been used to describe the controversial notion that smoking might improve cardiovascular outcomes post-AMI ( 44 , 45 ). However, conflicting evidence has emerged, refuting these paradoxical findings ( 46 48 ). Our data, assessed through Kaplan–Meier analysis, indicate no difference in plasma cotinine levels between patients with or without MACCE.…”
Section: Discussionmentioning
confidence: 99%